2012
DOI: 10.1063/1.4764520
|View full text |Cite
|
Sign up to set email alerts
|

A p-type Heusler compound: Growth, structure, and properties of epitaxial thin NiYBi films on MgO(100)

Abstract: Epitaxial semiconducting NiYBi thin films were directly prepared on MgO(100) substrates by magnetron sputtering. The intensity ratio of the (200) and (400) diffraction peaks, I(200)/I(400) = 2.93, was close to the theoretical value (3.03). The electronic structure of NiYBi was calculated using WIEN2k and a narrow indirect band gap of width 210 meV was found. The valence band spectra of the films obtained by linear dichroism in hard X-ray photoelectron spectroscopy exhibit clear structures that are in good agre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In zero field, ρ xx decreases in a metallic manner with the decrease of temperature, and a low residual resistivity of ρ xx (2K) = 0.082 mΩcm is obtained. This value is in the same order with that of YbPtBi, 25 but much lower than that of most reported half-Heusler compounds, such as YPtBi, 8 LuPdBi, 6 LuPtSb, 15,20 YNiBi, 26 and YPtSb, 27 implying a high sample quality. With the further decrease of temperature, ScPtBi single crystal shows no superconducting transition even at temperature down to 0.3K, which further confirms that there are no nano-scale bismuth inclusions trapped inside crystals.…”
mentioning
confidence: 46%
“…In zero field, ρ xx decreases in a metallic manner with the decrease of temperature, and a low residual resistivity of ρ xx (2K) = 0.082 mΩcm is obtained. This value is in the same order with that of YbPtBi, 25 but much lower than that of most reported half-Heusler compounds, such as YPtBi, 8 LuPdBi, 6 LuPtSb, 15,20 YNiBi, 26 and YPtSb, 27 implying a high sample quality. With the further decrease of temperature, ScPtBi single crystal shows no superconducting transition even at temperature down to 0.3K, which further confirms that there are no nano-scale bismuth inclusions trapped inside crystals.…”
mentioning
confidence: 46%
“…d states (A and B) with small binding energies have a higher intensity for s polarisation. As in other cubic Heusler compounds [26,64,65], the intensity of the a 1 states is suppressed by s polarisation, but it does not vanish, as expected for angular asymmetry parameter β 0 = 2 [66]. This is due to the sp-hybridisation of the states in the cubic symmetry.…”
Section: Haxpes Of the Valence Bandmentioning
confidence: 62%
“…The shape of the small pieces was fixed as a sector so that the depo- showed that the YPtSb thin films were p-type conductors with a high carrier density on the order of 10 20 − 10 21 cm −3 , which corresponded to the weak semiconducting behavior indicated by the resistivity curves. The weak temperature dependence of resistivity has also been observed in bulk YPtSb and other half-Heusler semiconductors [16], a trend markedly different from that in the case of conventional semiconductor materials such as Si. [10,[17][18][19] As seen in Fig.…”
Section: Resultsmentioning
confidence: 90%